Stress concentration factors (SCF) of CFRP-reinforced T/Y-joints via ZPSS approach. (1st October 2022) - Mohamed, H.S.; Yang, X.S.; Shao, Y.B.; Shaheen, M.A.; Suleiman, M.F.; Zhang, L.; Hossian, A.
Abstract: This research innovatively considers the Zero Point Structural Stress (ZPSS) approach to evaluate the stress concentration factors (SCFs) of the CFRP-reinforced T/Y-joints. To begin, multiple sets of credible experimental data and Finite Element (FE) results were selected to verify the accuracy of the proposed FE model. The comparison results showed that the ZPSS approach accurately estimated the SCF of tubular T/Y-joints reinforced with CFRP. Furthermore, the ZPSS approach, which considers the stress gradient through the thickness, shows more accurate results than the HSS approach, which considers only the stress at the outer surface of the chord. Then, 132 FE models were simulated to analyze the effects of the joint geometric dimensions and the CFRP laminates on the SCFs of the CFRP-reinforced tubular T/Y-joints. Finally, a parametric equation is proposed based on the FE results to predict the SCFs of tubular T/Y-joints reinforced with CFRP under axial compression loads. Highlights: The Stress Concentration Factors (SCF) of CFRP-reinforced tubular T/Y-joints were evaluated. The Zero Point Structural Stress Approach (ZPSS) was employed to determine the value of the SCFs. A comparison between the HSS brooch and ZPSS approach in calculating the SCFs was conducted. Parametric equations to predict the SCFs of CFRP-reinforced tubular T/Y-joints was established.